Hidden diversity in an ecologically specialized genus of Australian marsupials, the feather-tailed gliders, Acrobates (Diprotodontia, Acrobatidae) - Aplin, Kenneth P.; Armstrong, Kyle N.; Aplin, Lucy M.; Jenkins, Paula; Ingleby, Sandra; Donnellan, Stephen C. (Zootaxa, 2025)
The marsupial Family Acrobatidae includes the smallest gliding marsupial species in the monotypic Acrobates, found only in eastern Australia, and an equally small non-gliding species in another monotypic genus Distoechurus, found only in New Guinea. We applied molecular genetic analysis to Acrobates to assess the systematic significance of variation in superficial external characters of the tail and hindfoot (pes). Deep divergence in mitochondrial and nuclear genes demonstrated the broad sympatry of two species consistent with prior morphological diagnoses. Morphological assessment of museum vouchers showed that their distributions overlap extensively in New South Wales and Victoria and include locations where a range of biological research was conducted on the assumption of the presence of a single species. Many of these studies cannot be reassessed because neither vouchers nor tissue suitable for molecular genetic identification were collected. Intriguingly, acrobatids are the only marsupial group with internal ear discs, and the two species of Acrobates show demonstrable differences in the morphology of this structure, the biological significance of which needs to be established. Both species of Acrobates occur widely in the eucalypt forests of south-eastern Australia, which appear to be subject to a growing threat from bushfires likely aggravated by anthropogenic climate change.